A novel placement method of a calibration‐free pH capsule for continuous wireless measurement of intragastric pH in horses - Evelyn Hodgson; Marthe Thirouin; Pranav Narayanan; Tallia‐Rume Romano; Jessica Wise; Stephanie Bond (Journal of Veterinary Internal Medicine)
Abstract Background Current methods to measure intragastric pH in horses have limitations. A wireless capsule has been designed for continuous esophageal pH monitoring in humans. Objectives To (1) determine the feasibility and describe the methodology of measuring intragastric pH wirelessly in horses; and (2) determine attachment duration of the capsules. Animals Eleven healthy adult horses. Methods Capsules were attached to squamous and glandular gastric mucosa under gastroscopic guidance, using suture loops and 1 to 4 hemostasis clips. pH was continuously recorded using a wireless recorder in both fed and fasted states. Gastroscopy was performed daily to assess capsule attachment and any mucosal damage. Data were analyzed using commercially available software. Values are reported as median (interquartile range). Results Capsules were successfully placed and data obtained in squamous (n = 11) and glandular (n = 7) regions. The overall duration of squamous capsule attachment was 27 hours (15‐32); 1 clip (n = 4) was 15 hours (11‐20), 2 clips (n = 2) was 20 hours (16‐23), 3 clips (n = 4) was 32 hours (30‐32), and 4 clips (n = 1) was 33 hours. The overall duration of glandular capsule attachment was 10 hours (8‐21); 1 clip (n = 2) was 11 hours (10‐13), 2 clips (n = 2) was 19 hours (14‐23), 3 clips (n = 2) was 7 hours (7‐8), and 4 clips (n = 1) was 158 hours. There was no substantial damage to the gastric mucosa as a consequence of attachment. Conclusions and Clinical Importance This novel technique enables the wireless measurement of intragastric pH in horses at known locations under fed and fasted conditions, providing a viable alternative for continuous monitoring in both research and clinical scenarios.